Multiscale spatio-temporal dynamics of UBE3A gene in brain physiology and neurodevelopmental disorders - Biagioni, Martina; Baronchelli, Federica; Fossati, Matteo (Neurobiology of disease, 2024)
The UBE3A gene, located in the chromosomal region 15q11-13, is subject to neuron-specific genomic imprinting and it plays a critical role in brain development. Genetic defects of UBE3A cause severe neurodevelopmental disorders, namely the Angelman syndrome (AS) and the 15q11.2-q13.3 duplication syndrome (Dup15q). In the last two decades, the development of in vitro and in vivo models of AS and Dup15q were fundamental to improve the understanding of UBE3A function in the brain. However, the pathogenic mechanisms of these diseases remain elusive and effective treatments are lacking. Recent evidence suggests that UBE3A functions are both spatially and temporally specific, varying across subcellular compartments, brain regions, and neuronal circuits. In the present review, we summarize current knowledge on the role of UBE3A in neuronal pathophysiology under this spatio-temporal perspective. Additionally, we propose key research questions that will be instrumental to better understand the pathogenic mechanisms underpinning AS and Dup15q disorders and provide the rationale to develop novel therapies. •Genetic defects of the imprinted gene UBE3A cause neurodevelopmental disorders.•UBE3A critically regulate the function of distinct neuronal circuits and behaviors.•The molecular diversity of UBE3A is a key determinant of disease pathophysiology.•UBE3A operates during precise temporal windows to regulate neurodevelopment.